Influence of Labour Migration on the Rate of Youth Unemployment within the European Union: A Study Review - Pkhakadze Tamar (European Scientific Journal, ESJ, 2022)
The European Union has been working on migration issues for several years now and several policies and structures have been developed to better manage processes connected to migration. Legal labour migration remains one of the challenges and is still a very fragmented and limited process. For some specific categories, legal labour migration is much easier, for example, highly qualified workers, seasonal workers, students, researchers, etc. This paper focuses on finding the role of labour migration on unemployment. Paper analysis cases within the European Union and methodologies used are research based on primary or secondary sources (documents, literature). The methods used in this paper are mainly qualitative and include document and text analysis and some case studies. The approach does not refer to the main challenges of migration in the European Union as the labour market does not legally integrate migrants from outside Europe (for example, third-country nationals) and does not legally integrate family members of legally migrated people, asylum seekers or even students studying in the European Union member state.